Use of Force: Scot Harvath #16 - Thor, Brad; Schultz, Armand (New York, NY : Audioworks, Simon & Schuster Audio, 2017)
When the body of a high-value terrorist washes ashore during a storm in the Mediterranean Sea, Scot Harvath is hired by the CIA to determine if the suspect was involved in planning a major attack they've been fearing all summer.
Title from container.
Includes an interview with the author.
Read by Armand Schultz.
Keywords: Harvath, Scot (Fictitious character) -- Fiction; Intelligence officers -- United States -- Fiction; Terrorism -- Prevention -- Fiction; Suspense fiction; Audiobooks